Implementing Peer Assessment to Improve the Writing Ability of the Second Year Students of Smp Negeri 44 Muaro Jambi - Abdul Khalim (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
This research report is written to promote the use of peer assessment in EFL classrooms at SMP level. On the basis of a preliminary study done at SMPN 44 Muaro Jambi and the growing interest of the use of alternative assessment strategies led to the idea to conduct a study to implement an applicable and appropriate strategy of peer assessment to improve the writing ability of the second year students of SMPN 44 Muaro Jambi. The researcher designed a classroom action research (CAR) study. It began with a try out. A plan was then made in order the procedures implemented could facilitate the second year students of SMPN 44 Muaro Jambi to handle peer assessment properly and improve their ability in writing a descriptive paragraph as well. It was continued by implementing the plan, observing and evaluating or reflecting. The findings showed that the appropriate strategy of peer assessment in writing instructions to improve the students’ ability in writing a descriptive paragraph requires teachers to follow procedures; telling the purpose of conducting peer assessment, encouraging collaborative work, encouraging impartial assessment, giving clear and detailed guidelines, building students’ self confidence to write and assess, encouraging students’ self confidence to write and assess, and ensuring follow up tasks.